Primary School Problem Solving Question

This question can be solved using The Singapore maths bar method

Kieron has 3 Cats

Each a different weight

The first and second cat weigh 9kh altogether The second and third cat weigh 10kg altogether The first and third cat weigh 13kg altogether

How much does each cat weigh?

Answers
Singapore-maths-bar-method-answer.pdf
Sam P.
20 July 2016
Hi SamPlease see my solution using the Singapore maths bar method. Hope you find it useful in your teaching.
Sam P.
20 July 2016
Hi Sam,Try using simple algebra; make cat 1=x, cat 2 =y and cat 3 =z.You will now have 3 equations and three unknowns, for example, x+y=9, as can be derived from the first statement.Start by making x the subject of the first formula and sub this into the other equations.Things should then start to become clear...Let me know if you need further help.Kind regards, Chris
Chris B.
21 July 2016
Using algebra to prove the answerThe letters a, b and c represent the weights of the three cats in kg.These three equations come from the question:-  a + b =  7  b + c =  8  a + c = 11Subtract the second equation from the third equation:-  a – b =  3Add the first equation and the new equation together:-  a + b =  7  a – b =  3  ----------   add    2a = 10      a = 5From the first equation, b = 2From the third equation, c = 6
Damien C.
25 July 2016
Let cat1=acat 2 =bcat 3 =cthen,a+b=9b+c=10a+c=13subtract equation 3 from equation 1=> (a+b)-(a+c)=9-13=>b-c=-4add this to equation 2=> (b+c)+(b-c) = 10-4=>2b=6=>b=3.substitute the value of b in equation 1 we get,a+3=9=>a=6Substitute the value of b in equation 2, we get=>3+c=10=>c=10-3=>c=7Therefore, the first cat weighs 6kgs, the second cat weighs 3 kgs and the third cat weighs 7kgs.
sid92
03 August 2016
Leonora the Singapore bar method does not rely on guessing, unless of course you answer a different question and start with 4 cats and only 3 equations for which there are multiple solutions.Please do not post if you do not know what you are talking about. It is very unhelpful. Please instead try to understand the other solutions already posted.
Sam P.
01 September 2016
Assume the weight of the first cat is C1 kg, the second cat is C2 kg, the third cat is C3 kgC1+C2=9kg  (1)C3+C2=10kg  (2)C3+C1=13kg  (3)subtract (2) -(1) --> C3+C2-C1-C2=10-1 --> C3-C1=1kg  (4)add (3)+(4) --> C3-C1+C3+C1=13kg+1kg2xC3=14kg --> C3=7kg (weight of the third cat)C2=10kg-7kg=3kg (weight of the second cat)C1=13kg-7kg=6kg (weight of the first cat)
Wafaa K.
14 January 2017
Add an answer

Similar questions